1981
DOI: 10.1017/s0021859600036947
|View full text |Cite
|
Sign up to set email alerts
|

Yield and yield components of wheat (Triticum aestivum L.) and their interrelationships as influenced by nitrogen and seed rate in the Sudan

Abstract: Yield and yield components of wheat (Triticum aestivum L.) and their interrelationships as influenced by nitrogen and seed rate in the Sudan SUMMARY Field experiments were conducted for three seasons, 1971-2, 1972-3 and 1973-4 to study the effects of nitrogen fertilizer and seed rate and their interactions on grain yield and its components and attributes of growth of two wheat varieties, Giza 155 and Mexipak. The semi-dwarf Mexipak was found to be more responsive to nitrogen application than the taller Giza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
1

Year Published

1981
1981
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 10 publications
(8 reference statements)
2
6
1
Order By: Relevance
“…This could be due to the reason that increasing in planting density enhances the competition and the crops will suffer from starvation due to the shortage of food prepared in the leaf by the process of photosynthesis which leads to late maturity of the crop. The result of this study was in line with that of Osman and Mohamed (1981) who reported that abundant supply of seed rates delay physiological maturity in wheat. The result was also in agreement with Seleiman et al (2010) who reported that increasing seeding rates from 250-400 mG 2 grains prolong the number of days from sowing to maturity of wheat.…”
Section: Days To 90% Physiological Maturitysupporting
confidence: 91%
“…This could be due to the reason that increasing in planting density enhances the competition and the crops will suffer from starvation due to the shortage of food prepared in the leaf by the process of photosynthesis which leads to late maturity of the crop. The result of this study was in line with that of Osman and Mohamed (1981) who reported that abundant supply of seed rates delay physiological maturity in wheat. The result was also in agreement with Seleiman et al (2010) who reported that increasing seeding rates from 250-400 mG 2 grains prolong the number of days from sowing to maturity of wheat.…”
Section: Days To 90% Physiological Maturitysupporting
confidence: 91%
“…The small response probably occurred because available soil nitrogen content was high. The result disagreed with other reports that short cultivars responded more than tall cultivars to nitrogen fertilizer (OSMAN and MAHMOUD 1981, WATSON et al 1963, VoGELet al 1963). Nitrogen fertilizer increased several yield components, namely percentage fertile spikelets, spike length, harvest index, and kernel number per spike.…”
Section: Resultscontrasting
confidence: 98%
“…Three of the most important yield components of wheat are spikes per unit area, kernels per spike, and weight of kernels (SCHLEHUBER and TUCKER 1967). Those determinants of yield are affected both by genetic factors (SYME 1969, WALCorrand LAING 1976, SPIERTZ and VAN DE HAAR 1978 and agronomic practices (OSMAN and MAHMOUD 1981, WATSON et al 1963, VoGEL et al 1963, FARIS and DE PAUW 1981.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Crop response to SR can be measured by the analysis of plant morphological differences (Puckridge and Donald, 1967;Kirby, 1970;Kirby and Faris, 1972;Fischer et al, 1976), by examination of water and light differences in and around the crop (Kirby, 1970;Tompkins et al, 1991;Singh and Uttam, 1997), and by the different abilities of cultivars to compensate for low or high plant density (Osman and Mahmoud, 1981;Hassanein et al, 2001;Stephen et al, 2005).…”
Section: Introductionmentioning
confidence: 99%